Study of Brassica oleracea as Natural Alternative to Synthetic Indicator - Vijayanand, S.; Khalid, Mohammed (Asian Journal of Chemistry, 2018)
This study was carried out to screen indicator property of Brassica oleracea extracts which forms a natural alternative to chemical indicator. Phytochemical analysis of Brassica oleracea extracts revealed the presence of 9 phytochemical constituents. Further the extracts were screened for indicator property. Then natural indicator obtained from the extracts was also screened for estimations apart from regular acid-base titrations. In addition, natural indicator was also used to develop pH strips for determining the pH of commercial sample which includes colour change of pH strips shows significant result at different pH and may be used to measure pH of wide range of sample.